2001
DOI: 10.2307/3552374
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal to Reduce the Age Discrimination in Canadian Minor Hockey

Abstract: Pour un joueur canadien de hockey mineur, il existe un rapport étroit entre son mois de naissance et les chances qu'il aura de jouer dans une équipe de très haut niveau. Les joueurs nés dans les premiers mois de l'année sont avantagés. On attribue généralement ce fait au système de classification, dans le hockey mineur, qui groupe les joueurs en catégories selon l'âge. Dans cet article, nous commençons par un examen de la situation actuelle. Ensuite, nous montrons que le système de classification basé sur l'âg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 4 publications
2
45
0
12
Order By: Relevance
“…relative ratio of 1.31 (424 of 324), which is less than the ratio reported in other published studies. 10 The birth dates by quarter were not significantly different (p = 0. 19).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…relative ratio of 1.31 (424 of 324), which is less than the ratio reported in other published studies. 10 The birth dates by quarter were not significantly different (p = 0. 19).…”
Section: Discussionmentioning
confidence: 89%
“…The RAE was virtually identical for non-Canadian and non-North American players as it was for Canadian-born or trained players. The RAE should be re-examined if Hockey Canada follows through with plans to change the training system 10 to elucidate the effect of changes in policy. Musch and Grondin 19 reported that the increasing findings of an RAE suggested that a mixture of physical, cognitive, emotional and motivational causes work together to produce the effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between the solutions proposed by researchers for mitigate this effect these ones stand over the rest: to alternate the cutoff date (Hurley, Lior, & Tracze, 2001), to make competitions with younger age groups (Glamser, & Vincent, 2004), or to divide players from the same category in order to their performance (Kaiserman, 2005). However, all these propose will bang against handball philosophy and against IHF.…”
Section: Volume 12 | Issue 1 | 2017 | 321mentioning
confidence: 99%